For the First Time in Europe. Old Belief in Lithuania (1918–1923): Reemigration, Formation of Pomоrian Church Structures and Official Recognition of the Church - Potashenko, Grigoriy (Slavistica Vilnensis, 2025)
The article examines important aspects of the development of the Old Believers Church in Lithuania in 1918–1923 (mass reemigration, the formation of a complete Church structure, the basis of which was the Pomorian communities, and official recognition of the Church) and three closely interrelated problems. How the formation of new central structures of the Old Believers Church in Lithuania was associated with the reemigration of Old Believers, which contributed to the reconstruction of the former network of their communities, and with the subsequent legal recognition of the Old Believers Church in Lithuania in May 1923. Another problem is how the formation of a virtually unified Pomorian society took place. These aspects or themes of this study have not yet received consistent treatment in historiography.To analyse the religious and legal situation of the Old Believers Church in Lithuania, the works of historians, selected contextual historiography and studies of legal historians were involved. To compare the features of the legal status of the Old Believers Church in Lithuania in the regional context, foreign historiography is also involved, studying the legal status of Old Believers’ community in Poland, Latvia, Estonia and other countries. The official recognition of the Church became a landmark event in the history of the Old Belief, since Lithuania was the first state in Europe which formally recognized the autonomy and equality of the Old Believers Church in Lithuania. The article also uses the results of the author’s research in recent years, based on a complex of new archival materials, various documents, and ideas of historiography.
Keywords: The Old Believers Church; the Pomorians; the Fedoseyans; re-emigration; legal status; interwar Lithuania (without the Vilnius region)